Symbiosis of religious principles and basic occupational values on Islamic work-life balance - Abd. Rokis, Rohaiza (MIR Center for Social-Economic Research, 2014)
The presentation discusses some basic issues on work and life based on Islamic and non-religious principles. Work and life are inseparable facets of and for human existence. Work derives from the demands of life, and thus it becomes a responsibility for every individual person. The article attempts to relate some highlighted Qur’anic verses and Hadith with basic occupational values such as honesty, modesty and innovativeness, among others, at workplaces. In the end, it makes an effort to understand the working of the subconscious mind on work to make life worthwhile. The plan for this article is to lay emphasis that the presence of human beings, which includes their mind, energy and whatever they can offer in the forms of work, benefits all. In such a case, not only those humans may be seen as successful in fulfilling the work-needs, but also victorious in completing the life-demands as human beings. “Virtuous workplace” is the most ideal platform for such purpose.